Percepção de riscos de moradoras em áreas sujeitas a escorregamentos de encostas - Zandomenico, Jane [UNIFESP] (2019)
Introduction: Living in buildings in urban areas of slopes subject to landslides can cause direct and indirect impacts on health. The degree of impacts will depend on the magnitude of the occurrence of the disaster, the conditions for social and environmental vulnerability previously installed in the event and which increase the degree of exposure of the population and the capacities or measures taken to reduce potential risks and damage to the mental and physical health of those affected. In this scenario, the concept of risk can be inserted in different socio-cultural contexts, resulting in different life experiences, increasing or not the exposure to disasters. Objective: This dissertation aims to understand the place that environmental risk occupies in the lives of women living in the Buquirinha I and II neighborhoods, in the city of São José dos Campos, located in the State of São Paulo. Methods: The researcher was accompanied by community health agents to the mapped sites as very high-risk areas of landslide and conducted in-depth interviews with 12 dwellers and field ethnographic observations. Results: The collected data were analyzed in two topics: the first corresponds to the sociocultural context of the dwellers, which was understood through the categories: socio-economic conditions and access to leisure, home construction, family life, and community involvement, public infrastructure and health, perception of violence and of daily life, migrations, and suggestions to the public power. The second topic seeks to explain the place that the risk of slippery slopes occupies in the life of the dwellers. Conclusions: The data analysis showed that for ten interviewees the risk of slope slips is not perceived, because, in its sociocultural context, the risk originates from other sources, especially the loss of their dwellings due to the removal.